2020
DOI: 10.1371/journal.pone.0237610
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Facebook use and problematic video gaming as mediators of relationship between impulsivity and life satisfaction among female and male gamers

Abstract: Over the past few decades, many new technologies have emerged, such as portable computers, the internet and smartphones, which have contributed to improving the lives of individuals. While the benefits of these new technologies are overwhelmingly positive, negative consequences are experienced by a minority of individuals. One possible negative aspect of new technologies is their problematic use due to impulsive use which may lead to lower life satisfaction. The present study investigated the mediating role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 130 publications
(352 reference statements)
2
13
0
Order By: Relevance
“…Studies have demonstrated that life satisfaction is positively related to self-esteem (Cobos-Sanchiz et al, 2020;Saad, 2020), social self-efficacy (Bakioglu & Turkum, 2017;Ditchman et al, 2017;Jeon, 2016;Jian et al, 2018;Zamani & Shirazi, 2020), perceived social support (Cobos-Sanchiz et al, 2020;Malinauskas, 2010), optimism (Oriol et al, 2020;Türküm, 2005), self-control, and positive affection (Oriol et al, 2020). On the other hand, there are negative correlations between life satisfaction and psychological distress (Cobos-Sanchiz et al, 2020;Satici et al, 2020;Zhang et al, 2020), loneliness (Bakioglu & Turkum, 2017;Mellor et al, 2008), impulsivity, problematic video gaming (Cudo et al, 2020), and negative affectation (Deniz et al, 2012). Studies have shown that as individuals' social self-efficacy increases (starting and maintaining social relationships, etc.…”
Section: Satisfaction With Lifementioning
confidence: 99%
“…Studies have demonstrated that life satisfaction is positively related to self-esteem (Cobos-Sanchiz et al, 2020;Saad, 2020), social self-efficacy (Bakioglu & Turkum, 2017;Ditchman et al, 2017;Jeon, 2016;Jian et al, 2018;Zamani & Shirazi, 2020), perceived social support (Cobos-Sanchiz et al, 2020;Malinauskas, 2010), optimism (Oriol et al, 2020;Türküm, 2005), self-control, and positive affection (Oriol et al, 2020). On the other hand, there are negative correlations between life satisfaction and psychological distress (Cobos-Sanchiz et al, 2020;Satici et al, 2020;Zhang et al, 2020), loneliness (Bakioglu & Turkum, 2017;Mellor et al, 2008), impulsivity, problematic video gaming (Cudo et al, 2020), and negative affectation (Deniz et al, 2012). Studies have shown that as individuals' social self-efficacy increases (starting and maintaining social relationships, etc.…”
Section: Satisfaction With Lifementioning
confidence: 99%
“…Taking into account the breadth and consistency of the issues, only the variables concerning the relationship between the early maladaptive schemas and PFU among Polish Facebook users are examined in the present study. Additionally, the relationship between the multidimensional aspects of impulsivity and problematic behaviors was reported in another paper [61]. The dataset from the present study is available from the John Paul II Catholic University of Lublin repository database (accession link: http://hdl.handle.net/20.500.12153/1380).…”
Section: Participantsmentioning
confidence: 99%
“…The emerging area of research into Game Transfer Phenomena (GTP) examines the interplay between video game features, in-game experiences, and the manipulation of hardware, which can lead to sensory-perceptual and cognitive intrusions (e.g., hallucinations and recurrent thoughts) and self-agency transient changes (e.g., automatic behaviors) in relation to video games (Ortiz de Gortari, 2019b). It is only recently that GTP has started to be contextualized into research on gaming disorder to explain thought intrusions related to game content, reactivity to game-related cues, dissociation, and players' distinctive relationships with their avatars (Ahn et al, 2015;Cudo et al, 2020;Stavropoulos et al, 2020). Gaming disorder (GD) only affects a small minority of individuals (Kardefelt-Winther et al, 2017;Przybylski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%